Multimodal imaging–guided awake transnasal fiberoptic tracheal intubation in a patient with giant palatal pleomorphic adenoma: a case report - Zhang, Feng-Jiao; Zhou, Chao (Frontiers in Oncology, 2025)
We report the case of an 80-year-old male with a giant palatal pleomorphic adenoma (7.0 × 5.0 × 5.5 cm) that caused progressive dyspnea, dysphagia, and oropharyngeal airway distortion after 40 years of indolent growth. To our knowledge, this represents one of the largest documented cases in which awake transnasal tracheal intubation was performed for an intraoral tumor. Preoperative evaluation revealed nasopharyngeal-nasal junction narrowing, a mouth opening of 3 cm, Mallampati grade IV, and preserved glottic function. Multimodal imaging—including MRI, 3D CT reconstruction, and fiberoptic laryngoscopy—was critical in delineating tumor extent and airway anatomy, guiding a tailored airway management strategy. Awake transnasal fiberoptic tracheal intubation was performed via the right nostril using dexmedetomidine sedation, topical and regional anesthesia, and ultrasound-guided superior laryngeal nerve blocks. Intubation was successful on the first attempt, without the need for tracheotomy or procedural complications. The procedure lasted 90 minutes, with minimal blood loss and stable hemodynamics. The patient was extubated on postoperative day 1, discharged on day 10, and remained clinically stable at 6-month follow-up.